Implementasi Fusi Alam dan Budaya pada Desain Serak Owl dan Batik Sulawesi melalui Pembelajaran Centered Learning - Cindi Fatikha Aulia; Erna Setyowati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Indonesia possesses a wealth of natural and cultural resources that can be utilized as a source of inspiration for creative learning, particularly in the field of cosmetology. Integrating the two through an appropriate learning approach is expected to enhance students' creativity and skills. This study aims to determine the implementation of the fusion of nature and culture in Serak Owl and Sulawesi Batik designs through centered learning. The method used was descriptive qualitative, with 15 Beauty students from the class of 2022 as subjects. Data were collected through observation sheets using expert judgment and student response questionnaires, then analyzed using descriptive percentages. The results showed that the work quality test obtained an average score of 87.6%, categorized as very valid, while the liking test obtained a score of 93%, categorized as very liked. This indicates that the works are of high quality and very well received by respondents. The conclusion of this study is that the implementation of the fusion of nature and culture through a centered learning approach is effective in enhancing creativity, work quality, and the relevance of practice-based learning.